Potential of underground space energy storage and carbon reduction benefits of closed/abandoned mines in Anhui Province - Ke YANG; Jiale WEI; Qiang FU; Xin LV (Meitan kexue jishu)
With the continuous advancement of the “double carbon” goal, the construction of a new power system with renewable energy as the main body has become the core task of China’s energy transformation. The demand for large-scale and highly flexible energy storage technology is steadily on the increase, which provides an important development opportunity for the development of closed/abandoned mine pumped storage power stations. The potential of pumped storage construction in underground space of closed/abandoned mines in Anhui Province is evaluated in order to solve the constraints of site selection and other factors on the construction of traditional pumped storage power stations, explore the innovative path of green transformation of mining areas and coordinated development of new power systems, and promote the high-quality development of pumped storage in Anhui Province. The development planning of pumped storage power stations in recent years is summarized through bibliometrics and policy analysis, and the development trend of the construction of pumped storage power stations in closed/abandoned mines is analyzed. Combined with the pumped storage resource endowments such as the location of closed coal mines, the scale of underground space and the distribution of water resources in Anhui Province, the 60 closed/abandoned mines in the province in recent years are divided into three gradients according to the distance from the main water system: high potential area within 50 km, medium potential area within 50−100 km and low potential area outside 100 km, and typical mines are selected to carry out fine evaluation and discuss the construction scale of pumped storage power stations. Taking Zhuzhuang Coal Mine in Huainan-Huaibei Coal Mines mining area as an example, the feasibility of building pumped storage power station in Zhuzhuang Coal Mine is analyzed in detail from the aspects of underground available space and effective storage capacity of underground storage reservoir. The installed capacity of the proposed pumped storage power station in Zhuzhuang Coal Mine is designed to reach 17.87 MW. The carbon emission calculation model of closed/abandoned mine pumped storage power station is used to calculate the carbon emission reduction of 11300 t/d compared with traditional thermal power generation. The results show that the use of closed/abandoned mines to build pumped storage power stations can become an effective support for the development of new energy storage construction in Anhui Province, and make a positive contribution to the adjustment of energy structure and carbon neutrality in Anhui Province.